The breadwinner : a graphic novel - Tanaka, Shelley (Groundwood Books, House an Anansi Press, 2018)
Parvana, whose father was arrested by the Taliban, and whose family lives in one room of a bombed-out apartment building, must disguise herself as a boy to work and support her family.